A Learning Model for Children Aged 10-12 Years in Pencak Silat - Itus Apriyanti; Johansyah Lubis; Mastri Juniarto (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The objective of this study is to develop a new product for the martial sport of pencak silat that can be used by elementary school students during the learning process. This product will focus on paired inclusive learning for the straight kicks in pencak silat. The reason for this research is that many elementary school students struggle with straight kicks. This struggle starts from their initial attitude towards the technique and continues through the implementation and final attitude stages. These difficulties make the learning process boring for students and often result in an inability to properly focus on the technique, leading to poor form and unachieved learning objectives. Materials and methods. The study employs a combination of research and development methods aimed at creating a learning model product. This product will likely be the outcome of a rigorous process that involves research, experimentation, and testing to ensure that it meets the highest standards of quality and effectiveness. The learning model product could potentially be used to improve educational outcomes, enhance training programs, or facilitate knowledge transfer in various contexts. Results. Following validation by three experts, including lecturers specializing in pencak silat, learning, and PJOK, a comprehensive set of 14 models has been developed to enhance the learning of straight kick techniques. The models incorporate 5 initial stance models, 8 implementation stance models, and 1 final stance model. This research has culminated in the creation of a model book and learning video designed for children aged 10-12 years who are practicing pencak silat. Conclusion. After conducting a thorough validation process involving pencak silat expert lecturers, learning expert lecturers, and elementary school teachers, it has been determined that the pencak silat straight kick learning model is highly appropriate for children aged 10-12 years. The results indicate that this learning model can be effectively used as teaching material for straight kick training and can be easily understood and studied by students.